Human Semen Quality, Sperm DNA Damage, and the Level of Urinary Concentrations of 1N and TCPY, the Biomarkers of Nonpersistent Insecticides. Issue 1 (February 2019) - Dziewirska, Emila; Radwan, Michał; Wielgomas, Bartosz; Klimowska, Anna; Radwan, Paweł; Kałużny, Paweł; Hanke, Wojciech; Słodki, Maciej; Jurewicz, Joanna
The aim of the study was to evaluate the association between environmental exposure to nonpersistent insecticides and semen quality (concentration, motility, morphology, computer-aided semen analysis [CASA] parameters, and sperm DNA damage). Urine samples ( n = 315) collected from men who attended the infertility clinic with normal semen concentration of 15 to 300 mln/ml and age under 45 years were analyzed for two metabolites (1-naphthol [1N] and 3, 5, 6-trichloro-2-pyridinol [TCPY]) of nonpersistent insecticides. Participants provided semen, blood, and saliva samples; additionally, men filled a detailed questionnaire. The results identified that urinary TCPY concentration was significantly associated with a decrease in motility; also there was a positive association between TCPY and DNA fragmentation index (DFI). 1N concentration was negatively associated with a percentage of sperm with normal morphology and positively with one of the CASA parameters (curvilinear velocity [VCL]). The results suggest that environmental exposure to nonpersistent insecticides may have an impact on semen quality parameters and sperm DNA damage.